GSK-3 protein and the heart: friend or foe? - Huisamen, B.; Lochner, A. (SA Heart Journal, 2017)
Metabolic syndrome manifesting as obesity, insulin resistance and type 2 diabetes mellitus is currently pandemic. Each of these, in its own right, is strongly related to the development of cardiovascular disease. The cardiomyopathy associated with these disorders is characterised by curtailed glucose uptake and utilisation, elevated risk of damage after ischaemia and contractile dysfunction. Current research have indicated that the serine/threonine kinase, glycogen synthase kinase 3 (GSK-3), may play a central role in the development of all these dysfunctions. The development of new generations of inhibitors of this kinase, has renewed interest in its utilisation as therapeutic target. This review has therefore focused on the role of GSK-3 in the development of the obesity-related cardiomyopathy and has highlighted and discussed the detrimental as well as beneficial effects of the GSK-3 inhibitors that are currently available. We have discussed the different roleplayers such as the insulin signalling pathway, modulation of apoptosis and mitochondrial function, SERCA2 expression and regulation of the development of hypertrophy in the context of GSK-3 activity.